Antifungal and antioxidative potential of oil and extracts derived from leaves of Indian spice plant Cinnamomum tamala - Pandey, A. K.; Mishra, A. K.; Mishra, A. (Cellular and Molecular Biology, 2012)
Plant-based antimicrobials and antioxidants represent a vast untapped source for medicines and food supplements and hence have enormous therapeutic potential. Present work reports the fungicidal potential of Cinnamomum tamala Nees & Eberm (Lauraceae) leaf oil against five food spoilage and pathogenic fungi. In addition antioxidant efficacy of seven different solvent extracts derived from leaf was also evaluated using in vitro models. The oil demonstrated potent antifungal activity against Aspergillus niger, A. fumigatus, Candida albicans, Rhizopus stolonifer and Penicillium spp. in agar diffusion assay. Zone of inhibition ranged from 17-25 mm. The MFC values of oil against all the test fungi were found to be 230µg/ml. Phytochemicals present in C. tamala leaf were extracted in several solvents for assessing their effect in oxidative defense. The extracts exhibited appreciable antioxidant activity in Î²-carotene bleaching assay and reducing power assay. The antioxidative activities of extracts were compared with the activities of standard antioxidant compounds BHA and ascorbic acid. Petroleum ether, ethanol, acetone and chloroform extracts exhibited about 30-67% antioxidant activity in Î²-carotene bleaching assay. Aqueous and ethanol extracts exhibited better reducing power which increased gradually with increasing amount of the extract concentration showing dose dependent response. Results indicated that natural phytochemicals present in C. tamala leaf extracts have potential to prevent growth of food spoilage/pathogenic fungi. In addition they also have capability to mitigate the oxidative stress by antioxidant response.